2017
DOI: 10.1371/journal.pone.0181878
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thyroid hormones on patients with hepatocellular carcinoma

Abstract: Background & aimsHypothyroidism has recently been proposed as predisposing factor for HCC development. However, the role of thyroid hormones (TH) in established HCC is largely unclear. We investigated the impact of TH on clinical characteristics and prognosis of HCC patients.MethodsOf 838 patients diagnosed with nonsurgical HCC at the Division of Gastroenterology and Hepatology/Medical University of Vienna between 1992 and 2012, 667 patients fulfilled the inclusion criteria. The associations of thyroid functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 47 publications
1
30
1
1
Order By: Relevance
“…Compared with euthyroid subjects, hypothyroid patients had higher likelihood of advanced colonic disease (8.3 vs. 4.4%, p = 0.028) (185). In another study by Pinter et al, 667 patients diagnosed with non-surgically treated HCC were retrospectively followed for a mean period of 65.5 months (190). Hypothyroid patients (TSH>3.77 μU/ml) had a higher risk for large lesions (>5 cm), while Hyperthyroid patients (TSH<0.44 μU/ml) had a lower risk.…”
Section: Clinical Studies Of the Thyroid-cancer Associationmentioning
confidence: 99%
“…Compared with euthyroid subjects, hypothyroid patients had higher likelihood of advanced colonic disease (8.3 vs. 4.4%, p = 0.028) (185). In another study by Pinter et al, 667 patients diagnosed with non-surgically treated HCC were retrospectively followed for a mean period of 65.5 months (190). Hypothyroid patients (TSH>3.77 μU/ml) had a higher risk for large lesions (>5 cm), while Hyperthyroid patients (TSH<0.44 μU/ml) had a lower risk.…”
Section: Clinical Studies Of the Thyroid-cancer Associationmentioning
confidence: 99%
“…33 The studies have found that patients with high levels of TSH, the larger the tumor, the worse the prognosis. 34 In contrast, another independent study has shown that higher TSH or FT4 in the blood is associated with better clinical outcomes in HCC patients receiving chemotherapy. 25 Therefore, in our prospective cohort, we found that TSH level was associated with HCC progression, and patients with a high TSH level were at risk of tumor progression.…”
Section: Discussionmentioning
confidence: 95%
“…According to current understandings in this field, most of the literature has considered T3/T4 a potential tumor suppressor, while others have considered them to be oncogenic promoters in HCC (for a comprehensive review of the effects of thyroid hormones in HCC, see [112]). Some of these studies provided a possible explanation for the finding that higher TSH and free T4 levels in blood were associated with poorer prognoses and larger tumor size in unresectable HCC patients [113]. Intriguingly, another independent study showed that higher TSH or free T4 concentrations in blood were associated with better clinical outcomes in HCC patients receiving chemotherapy, but not sorafenib (a targeted anticancer drug) treatment [114].…”
Section: Liver Cancermentioning
confidence: 99%
“…As such, unless a specific liver or ovarian cancer delivering or targeting system can be developed, the TSHR-targeting strategy cannot be applied to extra-thyroid cancers. However, by use of the index obtained from the levels of TSH and free T4, one can select a better strategy to treat patients with HCC [113,114].…”
Section: Clinical Usefulness Of Tshr Related Pathways In Anticancer Tmentioning
confidence: 99%